INVESTIGASI PENERAPAN COLLABORATIVE LEARNING DI UNIVERSITAS BINA DARMA PALEMBANG - Intra Swadaya Hidayat; Muhammad Izman Herdiansyah (POSITIF : Jurnal Sistem dan Teknologi Informasi, 2020)
Abstract This study aims to investigate the extent of collaborative learning that occurs at Bina Darma University Palembang. The data used is data from posting in the e-learning forum. The data is then processed using the Community of Inquiry method approach. The results of this study are an analysis of the application of collaborative learning in e-learning forums and suggestions for improving its application. Keywords — LMS, Community of Inquiry, Blended Learning, Online Learning, Trancript Analysis